ECTHR_CHAMBER 10862/84 vom 12. Juli 1988 , AFFAIRE SCHENK c. SUISSE - Ecthr Chamber (1988)
Non-violation de l'art. 6-1;Non-violation de l'art. 6-2;Non-lieu à examiner l'art. 8; No violation: 6;6-1;6-2